EnvR is a potent repressor of acrAB transcription in Salmonella. (29th October 2022) - Blair, Jessica M A; Siasat, Pauline; McNeil, Helen E; Colclough, Abigail; Ricci, Vito; Lawler, Amelia J; Abdalaal, Hind; Buckner, Michelle M C; Baylay, Alison; Busby, Stephen J; Piddock, Laura J V
Abstract: Background: Resistance nodulation division (RND) family efflux pumps, including the major pump AcrAB-TolC, are important mediators of intrinsic and evolved antibiotic resistance. Expression of these pumps is carefully controlled by a network of regulators that respond to different environmental cues. EnvR is a TetR family transcriptional regulator encoded upstream of the RND efflux pump acrEF . Methods: Binding of EnvR protein upstream of acrAB was determined by electrophoretic mobility shift assays and the phenotypic consequence of envR overexpression on antimicrobial susceptibility, biofilm motility and invasion of eukaryotic cells in vitro was measured. Additionally, the global transcriptome of clinical Salmonella isolates overexpressing envR was determined by RNA-Seq. Results: EnvR bound to the promoter region upstream of the genes coding for the major efflux pump AcrAB in Salmonella, inhibiting transcription and preventing production of AcrAB protein. The phenotype conferred by overexpression of envR mimicked deletion of acrB as it conferred multidrug susceptibility, decreased motility and decreased invasion into intestinal cells in vitro . Importantly, we demonstrate the clinical relevance of this regulatory mechanism because RNA-Seq revealed that a drug-susceptible clinical isolate of Salmonella had low acrB expression even though expression of its major regulator RamA was very high; this was caused by very high EnvR expression. Conclusions: In summary, we show that EnvR is a potent repressor of acrAB transcription in Salmonella, and can override binding by RamA so preventing MDR to clinically useful drugs. Finding novel tools to increase EnvR expression may form the basis of a new way to prevent or treat MDR infections.